ECONOMIC ESSENCE, FORMS AND TYPES OF PAYMENTS FOR EMPLOYEE BENEFITS - Anzhelika Mashevska (Three Seas Economic Journal, 2022)
The article reveals the economic essence and importance of wages as a component of current payments to employees and studies the methodology and organization of accounting and taxation of remuneration. The problems of organization and methods of payroll accounting are determined. These are the main shortcomings in the field of taxation, as well as the problems of using the tariff system as the basis for accounting and documenting payments for remuneration with personnel. Methodology. The normative and legislative regulation of accounting and documentation of payments for remuneration is analyzed. The requirements for the formation of the organization of remuneration accounting, which determine the tasks, the system of indicators, documentation and the system of accounts on which the relevant information is accumulated, are presented. Results. It is concluded that the improvement of labor accounting and its remuneration at enterprises should be based on the optimization of tariff regulation of wages, namely: improvement of the tariff system by establishing ratios of tariff rates depending on the level of qualification of the worker; introduction of flexible forms and systems of remuneration, including contract and tariff-free; collective regulation of wages. The main ways to improve the display of wage accounting are proposed. Practical implications. The organization of document circulation on employee payments is investigated, the methodology of synthetic and analytical accounting of payments to employees for worked and unworked time is determined. The methodology of conducting audit procedures for payments to employees is considered, the effectiveness of employee benefits is evaluated. Value/originality. The scientific novelty of the work consists in summarizing theoretical and practical material on the methodology, economic essence, forms and types of payments for employee benefits. The theoretical essence of calculations on remuneration of the enterprise is determined, the regulatory and legal regulation of payments to employees in Ukraine is investigated, the tasks of accounting, auditing and analysis of employee benefits are considered.